Child, family, and narcissistic political leadership: a comparison of Hitler, Putin, and Trump - Çifci, Yusuf (Frontiers in Psychology, 2025)
IntroductionEvery person goes through a period of narcissistic development. Narcissism develops depending on whether children get balanced and adequate care during childhood. Children who get adequate and balanced care develop self-esteem and have constructive narcissistic qualities. Those who do not obtain adequate and balanced care are affected by narcissistic personality disorder and have reactive narcissistic characteristics. Political leaders are no exception to this rule; they were also once children and went through a stage of narcissistic development. This study aims to analyze how Hitler, Putin, and Trump completed their narcissistic developmental stages. In this regard, this study comparatively analyses the causes of these three individuals’ narcissistic political leadership related to their parents, families, and childhood.MethodsIt is not possible to apply psychological tests to political leaders, to sit them on Freud’s couch and psychoanalyse them. However, it is possible to find detailed information on the childhoods and families of political leaders. This study phenomenologically compares the familial reasons for the narcissistic political leadership of Hitler, Putin, and Trump on the basis of the available information. In this study, the phenomenological analysis technique was used based on qualitative information theory.ResultsHitler, Putin, and Trump grew up in similar families. When these three leaders are compared on the axis of familial causes of narcissism, it is seen that all three leaders were traumatized, experienced frustrations in their childhood that were not appropriate for their age, and grew up with an over-authoritarian father figure in addition to a mother who approached them with compassion. The fact that Hitler and Putin grew up as replacement children and were physically violated by their fathers, whereas Trump was placed in a boarding and disciplined military school at a precisely narcissistic developmental stage, triggered these three leaders to become narcissistic political leaders.DiscussionIt should not be forgotten that Hitler, as a narcissistic political leader, caused the deaths of millions of innocent people. In this sense, it is impossible to evaluate the policies implemented by political leaders and their leadership qualities apart from the family and childhood periods in which they grew up.